157k views
3 votes
What is the solution 3(2x-6)+4=8x-2(x+1)

1 Answer

2 votes

Answer:

Explanation:

3(2x-6)+4=8x-2(x+1)

We move all terms to the left:

3(2x-6)+4-(8x-2(x+1))=0

We multiply parentheses

6x-(8x-2(x+1))-18+4=0

We calculate terms in parentheses: -(8x-2(x+1)), so:

8x-2(x+1)

We multiply parentheses

8x-2x-2

We add all the numbers together, and all the variables

6x-2

Back to the equation:

-(6x-2)

We add all the numbers together, and all the variables

6x-(6x-2)-14=0

We get rid of parentheses

6x-6x+2-14=0

We add all the numbers together, and all the variables

-12!=0

User Rahul Dagli
by
4.1k points